Dose Reduction Technique Using a Combination of a Region of Interest (ROI) Material X-Ray Attenuator and Spatially Different Temporal Filtering for Fluoroscopic Interventions - Vasan, S.N Swetadri (2012)
We demonstrate a novel approach for achieving patient dose savings during image-guided neurovascular interventions, involving a combination of a material x-ray region of interest (ROI) attenuator and a spatially different ROI temporal filtering technique. The part of the image under the attenuator is reduced in dose but noisy and less bright due to fewer x-ray quanta reaching the detector, as compared to the non-attenuating (or less attenuating) region. First the brightness is equalized throughout the image by post processing and then a temporal filter with higher weights is applied to the high attenuating region to reduce the noise, at the cost of increased lag; however, in the regions where less attenuation is present, a lower temporal weight is needed and is applied to preserve temporal resolution. A simulation of the technique is first presented on an actual image sequence obtained from an endovascular image guided interventional (EIGI) procedure. Then the actual implementation of the technique with a physical ROI attenuator is presented. Quantitative analysis including noise analysis and integral dose calculations are presented to validate the proposed technique.